Aspects of violence: a critical theory - Schinkel, Willem (Cultural criminology series, 2010)
"While most analyses don't define violence and regard it as an essentially contested concept, this book argues for an ontological definition of violence as a reduction of being. This enables a critical sociology to move beyond tacit acceptance of a historically contingent definition of violence as profferred by the state"--Provided by publisher